Penerapan Kebijakan Moneter Islam pada Sistem Perekonomian Indonesia - Anisa Mawaddah Nasution; Maryam Batubara (Jurnal Penelitian Ekonomi Akuntansi, 2023)
Economic growth is a picture of the impact of government virtues that are carried out, especially in the economic field. The challenges facing the Islamic finance industry include resolving issues of form over substance, confronting value-based social and ethical finance, and strengthening public trust. These challenges can only be faced if Islamic finance is based on the monetary perspective of Islamic economics. Monetary policy aims to achieve and maintain rupiah stability. The study is based on an analysis of the literature on conventional monetary and Islamic monetary. Policy from an Islamic perspective has not been applied in jurisdictions in Indonesia's economic system. This purpose is as stated in Law No. 6 of 2009 in Article 7. The purpose of this journal is to find out about monetary policy from an Islamic perspective. This is interesting to discuss because there is a fundamental difference between conventional monetary policy and monetary policy from the perspective of Islamic economics